THE ROLE OF DIGITAL LITERACY IN ARABIC LANGUAGE LEARNING IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Rohmat, Basuki; Maulana, Asep; Huda, Mokhammad Miftakhul (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
The development of technology in the era of the Industrial Revolution 4.0 brings significant changes in the world of education, including in Arabic language learning. Digital literacy is an important skill that supports the teaching and learning process effectively and innovatively. This study aims to analyze the role of digital literacy in improving the quality of Arabic language learning at various levels of education. The research method used is a descriptive qualitative approach with data collection through interviews, observations, and literature studies. The results show that digital literacy facilitates access to learning resources, increases student motivation, and enables the application of technology-based learning methods such as e-learning and blended learning. In addition, the ability to integrate technology in Arabic learning helps students understand the material more interactively and contextually. This study concludes that digital literacy plays an important role in creating a more dynamic and adaptive learning experience according to the needs of the times. Therefore, it is necessary to develop digital literacy skills for educators and learners to optimize Arabic learning outcomes in the digital era.